2017
DOI: 10.9790/1676-1203053236
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Power System Transient Stability - A Review

Abstract: Intelligent-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study carried out by Airoboman et al (2015) showed that the Benin bus is the most sensitive in the NPS and as such, needs to be upgraded and compensated. Various studies have been done on the review of the application of controllers (Amaize et al 2017;Okakwu et al 2017) in the NPS as well as on load flow study (Agbontaen & Ike, 2017;Ogbuefi & Madueme, 2015;Onohaebi & Igbinovia, 2008;Onojo et al 2013). However, these studies were limited to the transmission 330kV lines only.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Airoboman et al (2015) showed that the Benin bus is the most sensitive in the NPS and as such, needs to be upgraded and compensated. Various studies have been done on the review of the application of controllers (Amaize et al 2017;Okakwu et al 2017) in the NPS as well as on load flow study (Agbontaen & Ike, 2017;Ogbuefi & Madueme, 2015;Onohaebi & Igbinovia, 2008;Onojo et al 2013). However, these studies were limited to the transmission 330kV lines only.…”
Section: Introductionmentioning
confidence: 99%